Efektivitas Pembelajaran Literasi Digital “Indonesian Fairy Tales” Melalui Metode Menyimak Terhadap Hasil Belajar Siswa - Silvia Anggraini; Yasir Arafat; Susanti Faipri Selegi (Jurnal Lensa Pendas, 2025)
This study aims to determine the effectiveness of digital literacy learning "Indonesian Fairy Tales" through the method of listening to student learning outcomes. The type of research uses a quantitative method with a Pre-Exsperimental Design with a One Group Pretest-Psttest Design. As for the subject of this study, there are 30 students in grade IV of SD Negeri 17 Palembang, the data collection method uses observation and tests, test instruments in the form of multiple-choice questions totaling 10 questions and essay questions totaling 5, to measure student learning outcomes data analysis techniques using the independent T-test. student learning outcomes.